The financing of the higher education: the diversification of sources - Шевченко, Л. С. (Theory and practice of jurisprudence, 2016)
In the article the essence and the principal models of the public financing of the higher education are analyzed. The ways of diversifying sources of the financing of the higher education are proposed. The conditions of the financing of the higher education in Ukraine are described. The necessity of attracting the householders and employers as private investors to finance the education industry is argued.